Congenital sideroblastic anemia treated as thalassemia major - Chowdhury, RK; Miah, MZ; Morshed, M (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):636-9 The abstract of this article is available on the PubMed website